(untitled) (Bangladesh Journal of Medical Science, 2014)
Objective: Continuous emergence of resistance among Pseudomonas aeruginosa strains to common antimicrobial drugs have been documented world-wide. This study investigated the recent trend of antimicrobial resistance patterns of P. aeruginosa among the patients in mid & far western region of Nepal. Materials and Methods: The study was conducted on 917 patients with suspected P. aeruginosa infections, attending outpatient and inpatient departments of Nepalgunj Medical College and teaching Hospital, Banke, Nepal from September 2011 to January 2014. Specimens were collected from pus/wound, sputum, urine, tracheal aspirates, central venous catheter tip, broncho-alveolar lavage fluid, catheters and vaginal swabs and processed for isolation and identification of P. aeruginosa following the standard microbiological methods. The disc diffusion test was used to determined antimicrobial resistance patterns of the recovered isolates at the central Laboratory of Microbiology. Results: One hundred ninety four isolates were identified as P. aeruginosa. Resistance to Chloramphenicol (74.23%), Ceftriaxone (69.56%), Cefepime (57.22%), Cefoperazone-Salbactum (54.12%) and Co-trimoxazole (53.02%) was observed. All the isolates were susceptible to Imipenem. 48 (24.74%) of P. aeruginosa isolates were multi-drug resistant to >3 classes of antibiotics. Among 194 isolates, 88 (45.36%) were from the patients of 21-40 years age group, which was statistically significant (P<0.05) compared to the other age groups. Conclusions: The study revealed the presence of drug resistant strains of P. aeruginosa in Nepal. High levels of antibiotic resistance of many of the isolates might be due to antibiotic abuse. Therefore, we recommend judicious use of antibiotics by the physicians to curb the increasing multi-drug resistance of P. aeruginosa strains in Nepal. DOI: http://dx.doi.org/10.3329/bjms.v13i4.20591 Bangladesh Journal of Medical Science Vol.13(4) 2014 p.438-442